Peningkatan Sadar Investasi Masyarakat melalui Model Penta Helix - Awwal, Muhammad Al Faridho; Rini, Dewi Wahyu Setyo (IQTISHODUNA, 2019)
In 2017, Indonesia takes the title of worth-invested country, supported by the fact that Indonesia has accredited by United Nation Conference on Trade and Developments (UNCTAD) as one of the countries with prospective investation target. Furthermore, investation also become an important part of Indonesian economy as President Joko Widodo said that investation become the key of improvement for Indonesian economy. Stock market’s growths in Indonesia is actually quite good, although its literacy rate is not so much. This research focused on strategy to grow the literacy rate of stock market in order to increase society’s awareness through the synergies and roles of stackholders. We take one of the government’s program which is Yuk Nabung Saham as the research’s object. Data that are being used here is in the form of primary data of interviews’ results and secondary data then described and interpreted. In the development of the said program, we used penta helix Model that involves five stackholders. Then, we used Laku Pandai program in collaboration with three stackholders. With this program we hoped that it could increase society’s awareness about the importance of investation especially on stock market and we also hoped that it could increase the number of society’s investment in Indonesia that could give good impact to the economy of the country.